Peraturan Daerah (Perda) sebagai Bagian Proses Manajemen Kebijakan Publik - Qotrunada, Arifah Sitta (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Brebes, 2023)
Local regulations are a product of public policies created by the government. Existing public policies must be in accordance with the circumstances and conditions of society. This means that every public policy must pay attention to all situations and conditions that are currently happening in society. If not, it is not impossible that a public policy will be rejected by the public. Public policies that do not pay attention to the values that live in society will affect the process of implementing policies, with conditions like this it is likely that policy implementation will be weak and not run optimally. Public policy is present in all government settings, starting from the local to the national level, which produces regulations and legislation. On this occasion the author will try to give examples of regulations that apply at the district level. In 2020, the Government of Banyumas Regency has issued Regional Regulation No. 2 of 2020. The background to the enactment of this regulation is that many people have started to ignore health protocols.